Development of Animal Model for Studying Deep Second-Degree Thermal Burns - Tavares Pereira, Danielle dos Santos (Hindawi Publishing Corporation, 2012)
Thermal lesions were produced in 12 male Wistar rats, positioning a massive aluminum bar 10 mm in diameter (51 g), preheated to 99°C ± 2°C/10 min. on the back of each animal for 15 sec. After 7, 14, 21, and 28 days, animals were euthanized. The edema intensity was mild, with no bubble and formation of a thick and dry crust from the 3rd day. The percentage of tissue shrinkage at 28 days was 66.67 ± 1.66%. There was no sign of infection, bleeding, or secretion. Within 28 days reepithelialization was incomplete, with fibroblastic proliferation and moderate fibrosis and presence of modeled dense collagen fibers. It is concluded that the model established is applicable in obtaining deep second-degree thermal burns in order to evaluate the healing action of therapeutic agents of topical use.